A monster calls [videorecording (DVD)] - Macdougall, Lewis; Weaver, Sigourney, 1949-; Jones, Felicity ([Publisher not identified], 2017)
Twelve-year-old Conor, dealing with his mother's illness, a less-than-sympathetic grandmother, and bullying classmates, finds a most unlikely ally when a monster appears at his bedroom window. Ancient, wild, and relentless, the monster guides Conor on a journey of courage, faith, and truth.